Systematic Review of Patient-Reported Outcomes and Complications of Pedicled Latissimus Flap Breast Reconstruction - Peshel, Emanuela C.; McNary, Claire M.; Barkach, Catherine; Boudiab, Elizabeth M.; Vega, Daniella; Nossoni, Farid; Chaiyasate, Kongkrit; Powers, Jeremy M. (Archives of Plastic Surgery, 2023)
The latissimus dorsi (LD) flap is a reliable option for breast reconstruction. This is particularly true in patients with contraindications to abdominally based autologous breast reconstruction. A systematic review of patient satisfaction and health related quality of life following LD breast reconstruction using the BREAST-Q survey was conducted. The scope of the review was to determine the degree of patient satisfaction following the procedure and to examine how patient satisfaction from the pedicled LD flap compares to other breast reconstructive procedures. A literature search on BREAST-Q in LD flap reconstruction was performed. Only articles written in English and in published peer-reviewed journals were included. Studies with less than 20 patients in their sample and those with a follow-up period of less than 1 year were excluded. Five articles representing 331 patients were reviewed, including one case–control study and four retrospective cohort studies. Level of evidence was either III (4) or IV (1). The average age was 53 with average body mass index of 25. Most reconstructions were delayed (67%) and unilateral (88%), and most patients required radiation (79%). The average length of follow-up was 36 months, and the response rate was 75%. Overall, patients who underwent LD flap reconstruction reported favorable outcomes in satisfaction domains and quality of life domains with few complications. A meta-analysis also demonstrated higher satisfaction in LD flap without implants compared with LD flap with implants. Patient-reported outcomes following LD breast reconstruction compare favorably with other techniques of breast reconstruction.
Keywords: breast reconstruction; latissimus dorsi flap; BREAST-Q; patient satisfaction